O‘QUVCHILARNING O‘QUV YUTUQLARINI BAHOLASHDA «GOOGLE FORMS»NING IMKONIYATLARIDAN FOYDALANISH - Pardayev, Sh.M. (SCIENCE and SOCIETY, 2024)
This article discusses the use of the online service Google Forms for online monitoring and evaluation of students' knowledge, skills, and abilities.
Keywords: assessment; formative assessment; summative assessment; online control; Google Forms; test